МАКТАБГАЧА ТАЪЛИМ ТИЗИМИДА ЖИСМОНИЙ ТАРБИЯНИ ТАШКИЛ ЭТИШНИНГ ИММАНЕНТ ХУСУСИЯТЛАРИ - Рахимов, В. (SCIENCE and SOCIETY, 2020)
The article reveals the features and immanent properties of physical education in the system of preschool education, as well as the morphofunctional and psychophysiological features of pupils of pre-school educational institutions. Methodological recommendations on the formation of interests of preschool children to physical exercises are offered.
Keywords: preschool education; children; physical education; physical exercises; morphofunctional; psychophysiological features; interests; running; adaptation; immanent; hardening